Soil Organic Carbon and Soil Bio‐Physicochemical Properties as Co‐Influenced by Tillage Treatment. Issue 5 (2nd October 2015) - Fontana, Mario; Berner, Alfred; Mäder, Paul; Lamy, Frederic; Boivin, Pascal
Abstract : Soil conservation practices are growingly used with different aims such as reducing fuel consumption and preserving soil organic carbon (SOC). Among others, reduced tillage (RT) often replaces conventional tillage (CT). However, the compared impact of these practices on soil quality remains a matter of controversy. Moreover, the various changes expected are rarely considered all together though they are known to interact. This study aimed at characterizing together the changes in SOC, microbial activity, and a large set of physical properties when comparing RT and CT performed on a clayey soil. Shrinkage analysis allowed to characterize simultaneously the soil pore systems, their volume, air and water content, the hydro‐structural stability, and the swelling properties of the soil. Analysis of covariance (ANCOVA) was used to compare the soil properties taking in account clay content variability. We showed that clay and SOC changes induced most of the variance of the other parameters. At standardized clay content SOC was increased with RT in the topsoil and homogenized with smaller values in the CT layer. Many soil physical and biochemical properties were enhanced accordingly with RT which induced a more stable soil with increased porosity and improved microbial activity. Sharp changes in soil quality seem to occur at the CT plow limit, while smooth changes with depth are observed with RT. Independently from the SOC increase with RT, changes in physical properties and microbial activity could be due to mechanical stress in CT or changes in organic matter quality in RT.